Neuroprotective Effect of Astragaloside IV on Cerebral Ischemia/Reperfusion Injury Rats Through Sirt1/Mapt Pathway - Shi, Yi-Hua; Zhang, Xi-Le; Ying, Peng-Jie; Wu, Zi-Qian; Lin, Le-Le; Chen, Wei; Zheng, Guo-Qing; Zhu, Wen-Zong (Frontiers in Pharmacology, 2021)
Abstract Background: Ischemic stroke is a common disease with poor prognosis, which has become one of the leading causes of morbidity and mortality worldwide. Astragaloside IV (AS-IV) is the main bioactive ingredient of Astragali Radix (which has been used for ischemic stroke for thousands of years) and has been found to have multiple bioactivities in the nervous system. In the present study, we aimed to explore the neuroprotective effects of AS-IV in rats with cerebral ischemia/reperfusion (CIR) injury targeting the Sirt1/Mapt pathway. Methods: Sprague-Dawley rats (male, 250-280g) were randomly divided into the Sham group, middle cerebral artery occlusion / reperfusion (MCAO/R) group, AS-IV group, MCAO/R + EX527 (SIRT1-specific inhibitor) group, and AS-IV + EX527 group. Each group was further assigned into several subgroups according to ischemic time (6h, 1d, 3d, and 7d). The CIR injury was induced in MCAO/R group, AS-IV group, MCAO/R + EX527 group, and AS-IV + EX527 group by MCAO surgery in accordance with the modified Zea Longa criteria. Modified Neurological Severity Scores (mNSS) were used to evaluate the neurological deficits; TTC (2,3,5-triphenyltetrazolium chloride) staining was used to detect cerebral infarction area; Western Blot was used to assess the protein levels of SIRT1, acetylated MAPT (ac-MAPT), phosphorylated MAPT (p-MAPT), and total MAPT (t-MAPT); Real-time Quantitative Polymerase Chain Reaction (qRT-PCR) was used in the detection of Sirt1 and Mapt transcriptions. Results: Compared with the MCAO/R group, AS-IV can significantly improve the neurological dysfunction (P<0.05), reduce the infarction area (P<0.05), raise the expression of SIRT1 (P<0.05), and alleviate the abnormal hyperacetylation and hyperphosphorylation of MAPT (P<0.05). While compared with the AS-IV group, AS-IV+EX527 group showed higher mNSS scores (P<0.05), more severe cerebral infarction (P<0.05), lower SIRT1 expression (P<0.01), and higher ac-MAPT and p-MAPT levels (P<0.05). Conclusion: AS-IV can improve the neurological deficit after CIR injury in rats and reduce the cerebral infarction area, which exerts neuroprotective effects probably through the Sirt1/Mapt pathway.